2013
DOI: 10.1007/s00449-013-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative production of shikimic acid: a paradigm shift of production concept from plant route to microbial route

Abstract: Different physiological and nutritional parameters affect the fermentative production of shikimic acid. In our study, Citrobacter freundii initially produced 0.62 g/L of shikimic acid in 72 h. However, when process optimization was employed, 5.11 g/L of shikimic acid was produced in the production medium consisting of glucose (5.0 %), asparagine (4.5 %), CaCO3 (2.0 %), at pH 6.0, when inoculated with 6 % inoculum and incubated at 30 ± 1 °C, 200 rpm for 60 h. Preliminary fed-batch studies have resulted in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Therefore, it remains to investigate the hypothesis of a possible microbial process responsible for the increase of shikimic acid. Recently (Tripathi et al, 2013) have shown that strains of bacterium Citrobacter freundii can produce 9.11 g/L of shikimic acid from 20 g/L of glucose in suitable conditions of fermentation. However, a preliminary microbial analysis of the fermenting must in a laboratory has not revealed the presence of this organism.…”
Section: Shikimic Acid In Aglianico Del Vulturementioning
confidence: 99%
“…Therefore, it remains to investigate the hypothesis of a possible microbial process responsible for the increase of shikimic acid. Recently (Tripathi et al, 2013) have shown that strains of bacterium Citrobacter freundii can produce 9.11 g/L of shikimic acid from 20 g/L of glucose in suitable conditions of fermentation. However, a preliminary microbial analysis of the fermenting must in a laboratory has not revealed the presence of this organism.…”
Section: Shikimic Acid In Aglianico Del Vulturementioning
confidence: 99%
“…4,13,52 Although several routes have been described for chemical synthesis, production of SA acid by these methods is too expensive and/or generates waste containing environmental pollutants; therefore, these are not commercially viable. 4,10,[53][54][55][56][57][58][59] Because plants synthesize aromatic amino acids and most polycyclic compounds by their SA pathway, the yield of SA from this source can vary; the factors that influence the yield include the time of harvest, handling, storage, plant tissue, and other factors that regulate plant metabolism resulting in the accumulation of SA in tissues where metabolic processes have slowed or stopped, such as seeds and fruits.…”
Section: Sa Production Extraction From Plant Sourcesmentioning
confidence: 99%
“…4,10 Because of this important application, the production of SA from different sources has gained great attention and has been extensively reviewed. 4,[10][11][12][13] Scientific and industrial interest in the ASA pathway is mainly focused on the production of AHBA as the precursor for the synthesis of aminoglycoside antibiotics; 5,7,9,14 however, another intermediate of this pathway, ASA, is an attractive candidate for use as the core scaffold for the synthesis of combinatorial libraries alternative to SA as a precursor for the synthesis of OSP. 14 In this review, we discuss the relevance of the key intermediates SA and ASA as scaffold molecules for the synthesis of diverse chemicals; their current and potential pharmaceutical applications; current strategies for the production of these aromatic compounds from natural sources; and the application of metabolic engineering strategies in diverse bacterial strains for production through biotechnological processes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, genetically modified E. coli strains can overproduce SHK from glucose with yields in the range of 0.08 to 0.42 mol SHK / mol glucose under diverse culture conditions [28,50,[68][69][70]. SHK is a key intermediate of the common biosynthetic aromatic pathway ( Figure 1) gaining relevance as the substrate for the chemical synthesis of the drug oseltamivir phosphate, known commercially as Tamiflu®, an efficient inhibitor of the surface protein neuraminidase of seasonal influenza, avian influenza H5N1, and human influenza H1N1 viruses [71][72][73][74].…”
Section: Introductionmentioning
confidence: 99%